2020
DOI: 10.17533/udea.ikala.v25n02a03
|View full text |Cite
|
Sign up to set email alerts
|

Content and Language Integrated Learning: In-Service Teachers’ Knowledge and Perceptions Before and After a Professional Development Program

Abstract: This mixed-methods study investigated perceptions and knowledge about content and language integrated learning (CLIL) and bilingual education. Data were collected using surveys, questionnaires and semi-structured interviews from 26 content-based teachers in Valledupar, Colombia, before and after their participation in an online training program. Findings revealed that teamwork and administrative support are crucial factors for a successful CLIL implementation. However, results also showed that teachers knew ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 36 publications
0
11
0
1
Order By: Relevance
“…However, it is possible that teachers can learn this method in-service, on the job. This was the finding of McDougald & Pissarello (2020) when they investigated teachers on the use of the CLIL method. They found that most teachers were not trained on the CLIL method until they started at their teaching jobs.…”
Section: Resultsmentioning
confidence: 96%
“…However, it is possible that teachers can learn this method in-service, on the job. This was the finding of McDougald & Pissarello (2020) when they investigated teachers on the use of the CLIL method. They found that most teachers were not trained on the CLIL method until they started at their teaching jobs.…”
Section: Resultsmentioning
confidence: 96%
“…Collaborative competence was mentioned in 13 studies on teachers' needs. Although a few studies reported collaboration among CLIL teachers (Pavón Vázquez et al, 2020;Pérez Cañado, 2017), the majority indicated that teachers were not collaborative, despite teachers seeing the need for collaboration (e.g., Fernández & Halbach, 2011;Infante et al, 2009;McDougald & Pissarello, 2020). The reasons that teachers are reluctant to collaborate include the lack of time (Bárcena Toyos, 2017), the tension between content and language teachers (McDougald & Pissarello, 2020), and the lack of opportunities to collaborate (Pladevall-Ballester, 2015).…”
Section: Collaborative Competencementioning
confidence: 99%
“…Other studies called for in-cluding a pedagogical component in professional development training for CLIL teachers. In fact, pedagogical training topped the list of needs in Durán-Martínez and Beltrán-Llavador's (2016) study, whereas approximately one-third of the participants in Fernández and Halbach's (2011) study called for the inclusion of methodology in their training.Likely responding to the strong desire by CLIL teachers to receive pedagogical training, the programs inCammarata and Haley (2018),Francomacaro (2019),Lo (2019), and McDougald and Pissarello (2020 all worked to develop the pedagogical competence of CLIL teachers. These workshops focused on instructional techniques(Mc- Dougald & Pissarello, 2020) and scaffolding strategies…”
mentioning
confidence: 99%
“…Mancipe Triviño and Ramírez Valenzuela (2019) report on using CLIL to teach natural science in a bilingual school in Colombia. McDougald and Pissarello (2020) conducted a teacher training course on CLIL and concluded that teachers found similarities between CLIL and bilingualism.…”
Section: Implementing Bilingualism In Real Settingsmentioning
confidence: 99%